The Utility of Cognitive Screening in Asian Patients With Heart Failure: A Systematic Review - Niu, Qi; Liu, WeiHua; Wang, FengLing; Tian, LiYa; Dong, YanHong (Frontiers in Psychiatry, 2022)
Abstract Background: The prevalence of undiagnosed cognitive impairment in heart failure patients is alarmingly high in Asia. There is still no consensus on cognitive screening tools to detect cognitive impairment in Asian heart failure population. The clinical implications based on our systematic review may help to improve cognitive screening practice for heart failure patients in Asia. Methods: This review is registered in PROSPERO (CRD42021264288). Using a PRISMA approach, we searched PubMed, Embase, Cumulative Index to Nursing and Allied Health Literature, Scopus, Web of Science, PsycINFO, Cochrane Central Register of Controlled Trials, China National Knowledge Infrastructure, and Wanfang Data in English and Chinese literatures concerning heart failure and cognitive impairment. Results: The search yielded 21 eligible studies. Only in five studies, cognitive brief tests including MoCA, MMSE and Mini-Cog, were used as cognitive screening tools for Asian patients with heart failure. In the rest 16 studies, brief cognitive tests were used as screening tools of global cognition. Only one study validated screening tests against a gold standard formal neuropsychological assessment test battery. Among these studies, heart failure patients tended to perform worse than patients without heart failure. The presence of cognitive impairment in heart failure patients is associated with poorer self-care, quality of life and hospital readmission. Conclusion: Brief cognitive tests have been used in Asian heart failure patients, and these tests are frequently used as a measure of global cognitive function for cognitive screening. However, validating brief cognitive tests against a gold standard formal neuropsychological assessment in Asian heart failure patients is lacking. Future studies need to address methodological issues to validate cognitive screening measures in a larger population of Asian patients with heart failure.